1996
DOI: 10.1037/1040-3590.8.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Trauma-Related Guilt Inventory (TRGI).

Abstract: The article describes the development and psychometric evaluation of the Trauma-Related Guilt Inventory {TRGI). An initial questionnaire was constructed from multiple sources of information. Three factor analytic studies were conducted to refine the TRGI and determine its factor structure, which consists of a Distress factor and three cognitive factors, Hindsight-Bias/Responsibility, Wrongdoing, and Lack of Justification. The TRGI has high internal consistency and adequate temporal stability. In validity studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
401
1
19

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(429 citation statements)
references
References 96 publications
8
401
1
19
Order By: Relevance
“…These effects were observed on the 'hindsight bias' and 'lack of justification' scales of the Trauma-Related Guilt Inventory (TRGI; Kubany et al, 1996). Relative to PE, CPT therapy completers demonstrated effect sizes ranging between 0.47 and 1.03 on these guilt measures at posttreatment and at a 9-month follow-up.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…These effects were observed on the 'hindsight bias' and 'lack of justification' scales of the Trauma-Related Guilt Inventory (TRGI; Kubany et al, 1996). Relative to PE, CPT therapy completers demonstrated effect sizes ranging between 0.47 and 1.03 on these guilt measures at posttreatment and at a 9-month follow-up.…”
Section: Introductionmentioning
confidence: 89%
“…Large effect sizes were observed when CPT and PE completers were compared with a minimal attention control group, with effect sizes ranging between 0.73 and 2.02 at posttreatment. When compared with the normative data (Kubany et al, 1996), it can be seen that participants who completed therapy reported pretreatment guilt at levels equal to or higher than treatmentseeking Vietnam veterans and victims of intimate partner violence. Furthermore, levels of guilt at posttreatment and follow-up fell below the mean levels reported for college students exposed to trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The Trauma-Related Guilt Inventory (TRGI; Kubany et al, 1996) is a 32-item self-report measure assessing guilt experienced in relation to a specific traumatic event. Items are scored on a 5-point scale ranging from 4 ( extremely true ) to 0 ( not at all true ) and the measure includes three scales: (a) a four-item Global Guilt scale, measuring the magnitude of guilt experienced after a traumatic event; (b) a six-item Distress scale, measuring physical distress specifically related to the trauma memory; and (c) a 22-item Guilt Cognitions scale, measuring participants’ beliefs that their thoughts, feelings, or actions have violated personal and/or moral standards of behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…According to the model, a traumatic event can cause individuals to experience severe feelings of guilt, the degree of which depends on the perceived personal involvement. The evaluation of personal involvement may be influenced by factors such as perceived wrongdoing, responsibility, and self-blame (Foa & Rothbaum, 1999; Kubany et al, 1996). Feelings of guilt, in turn, may form the basis of trauma-related intrusions typical of PTSD symptomatology (Lee et al, 2001).…”
mentioning
confidence: 99%
“…Independently, CSB-related attributions may affect the nature of the shame response, for example, strengthening its intensity or chronicity. CSB-related attributions also can affect guilt's intensity or chronicity (see Kubany, Haynes, Abueg, & Manke, 1996;O'Connor, Berry, & Weiss, 1999), although this connection is not normally identified in the mainstream empirical literature.…”
Section: Shame: Regulatory Goals and Motives (Assumption I)mentioning
confidence: 99%